Pengaruh Efikasi Diri dan Motivasi Kerja Terhadap Kinerja Guru Sekolah Taman Kanak Kanak Di Kecamatan Medan Area - Saibatul Aslamiyah; Lahmuddin Lahmuddin; Sjahril Effendy (Universitas Medan Area, 2020)
The purpose of this study was to see the effect of self-efficacy and work motivation on the performance of kindergarten school teachers in Medan Area District. The population in this study were 99 people who were teachers from 42 kindergartens in Medan Area District. The hypothesis proposed in this study, namely: 1). There is an effect of self-efficacy on the performance of kindergarten teachers in Medan Area District. 2). There is an influence of work motivation on the performance of kindergarten teachers in Medan Area District. 3). There is an influence of self-efficacy and work motivation on the performance of kindergarten teachers in Medan Area District. To prove that hypothesis is used the Anareg formula, which based on the results of the analysis obtained results: 1). there is a very significant effect between self-efficacy and work motivation on performance. This result is indicated by the Freg coefficient = 35,351; sig 0.010. 2). there is a very significant effect between self-efficacy and performance. This result can be seen from the correlation coefficient rx1y = 0.637; sig 0,000. 3). there is a very significant effect between work motivation and performance, where rx2y correlation coefficient = 0.446; sig 0,000. From these three results, it can be stated that the proposed hypothesis is declared accepted